Carbon footprint and water footprint analysis of generating synthetic natural gas from biomass. (March 2022) - Yao, Dong; Xu, Zaifeng; Qi, Huaqing; Zhu, Zhaoyou; Gao, Jun; Wang, Yinglong; Cui, Peizhe
Abstract: Bioenergy is generally considered clean and renewable. Water and energy are necessary for producing natural gas from biomass. Analyzing the carbon footprint of the life cycle and water footprint of producing natural gas from biomass can help in the efficient utilization of renewable energy. Carbon dioxide emissions and water consumption in biomass pyrolysis gasification were analyzed. The results showed that the water footprint of natural gas production from biomass is 15.38 L/MJ over its life cycle and that its carbon footprint is 159.24 kg/GJ. Wheat production is the dominant factor in total water consumption, accounting for 98% of the total value. Direct carbon emissions in the natural gas production stage are the main contributor to total emissions, accounting for 69.02% of the latter; water consumption in this process accounts for only 1.06% of the total water use. The effect of eight power generation modes on the total water footprint is small, while their effect on the carbon footprint is large (increments of −3 to −9%). In addition, the effects of 24 scenarios on the final results were investigated through a sensitivity analysis. This study presents relevant carbon emission and water consumption values for a certain range of biomass-to-natural gas production processes. The results obtained herein provide a reference for lowering resource consumption as part of natural gas production and developing environmental investment plans and policies.